PTU-280 Establishing eligibility for case discussion in multidisciplinary team care within an inflammatory bowel disease service provision – results from a qualitative two-stage expert based study. (22nd June 2015) - Morar, P; Sevdalis, N; Read, J; Arora, S; Warusavitarne, J; Hart, A; Green, J; Edwards, C; Faiz, O
Abstract : Introduction: Multidisciplinary Team (MDT) driven care is arising intuitively within the Inflammatory Bowel Disease (IBD) setting. There are no clear evidence-based definitions of what cases are eligible for discussion in the IBD MDT. Providing a standardised framework, with a clearly defined eligibility criteria, may enhance its capacity to establish effective quality improvement. This study aimed to obtain a definition of IBD patients for discussion in the MDT, through expert-based consensus. Method: This was a prospective, multi-centre, two-stage qualitative study. Stage 1 used semi-structured interviews across a multi-disciplinary sample of 28 participants. Items identified were incorporated into stage 2. Stage 2 used a Delphi formal consensus-building methodology. An eligibility criterion was established to ensure Delphi panellists had expertise in the field of IBD. Panellists were asked to rank each item with a Likert scale which was categorised from 1 (= not relevant) to 5 (= highly relevant). Successive rounds were carried out, with participants being informed of aggregated responses, until formal consensus was reached. Likert ratings were represented with median scores and interquartile ranges (IQR). Consensus was defined with an IQR ≤ 1. Items with a median score > 3, and IQR ≤ 1, were included into the eligibility criteria. Results: Stage 1: Thematic saturation was achieved after 28 semi-structured interviews (6 colorectal surgeons, 6 IBD nurse specialists, 7 gastroenterologists, 5 radiologists and 4 histopathologists). Table 1 demonstrates items identified. Stage 2: A multidisciplinary sample of 24 experts were recruited. Items [median; IQR] acheiving consensus were complex cases requiring surgery [4; 1], patients on biological therapy [4; 1], newly diagnosed IBD cases [4; 1], and patients with recent surgery [3.5; 1] . Conclusion: Patients eligible for discussion in the IBD MDT should have complex IBD requiring surgery, be on biologics, be newly diagnosed with IBD, or have undergone recent IBD surgery. This consensus-derived eligibility criteria provides a focus for core members, enhancing the MDT as a tool that delivers a high quality IBD service provision. Further validation of this criteria is required prior to implementation into standards. Disclosure of interest: None Declared.